THE INTERPRETATION OF THE “PICTURES OF LATE TIME“ (JAN KALINCIAK: RESTAVRACIA /RESTORATION/) - René Bílik (Slovenska Literatura, 2010)
The study is an interpretation of one of the most known texts of the Slovak Romantic literature, the fiction of Ján Kalinčiak Reštavrácia (Restoration). The main problem initiating the interpretation is an opinion, quite fixed by the history of literature and also known in the school praxis, that the mentioned fiction has a realistic character. Contrary to it, the author of the study, however, pointed out mainly features connected with the Romanticism. He shows constitutive role of the rational scepsis in the text. He defines it as basic semantic gesture of Ján Kalinčiak not only for this fiction but also for his historical fictions. Those are helpful as a “paradigm” of methods and conventions for reading the Reštavrácia (Restoration). The study discloses foundational features of “picture” in the structure of Kalinčiak´s fiction and it shows connections with early Romanticism in the concept of Romantic irony.